A Real-Business-Cycle model with robots: Lessons for Bulgaria - Vasilev, Aleksandar (Journal of Mathematical Economics and Finance; Vol 7 No 2 (2021): JMEF, Volume VII, Issue 2(13), Winter 2021, 2021)
Robots are introduced into a real-business-cycle setup augmented with a detailed government sector. Robots are modeled as an imperfect substitute for labor services. The model is calibrated to Bulgarian data for the period following the intro- duction of the currency board arrangement (1999-2020). The quantitative importance of the presence of robots in the economy is investigated for business cycle fluctuations in Bulgaria. In the presence of robots, wages increase, but employment falls after a technology shock. However, for plausible parameter values, the effect is predicted to be quite small.